2004
DOI: 10.1091/mbc.e03-10-0733
|View full text |Cite
|
Sign up to set email alerts
|

Rabenosyn-5 and EHD1 Interact and Sequentially Regulate Protein Recycling to the Plasma Membrane

Abstract: EHD1 has been implicated in the recycling of internalized proteins to the plasma membrane. However, the mechanism by which EHD1 mediates recycling and its relationship to Rab-family-controlled events has yet to be established. To investigate further the mode of EHD1 action, we sought to identify novel interacting partners. GST-EHD1 was used as bait to isolate a approximately 120-kDa species from bovine and murine brain cytosol, which was identified by mass spectrometry as the divalent Rab4/Rab5 effector Rabeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
203
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(215 citation statements)
references
References 54 publications
12
203
0
Order By: Relevance
“…In addition, EHD1/mRme-1 interacts through its EH domain with an actin-associated protein EHBP1 that, like EHD1/mRme-1 itself, is required for insulinstimulated translocation of the GLUT4 to the plasma membrane (13). Finally, EHD1/mRme-1 has been shown to interact through its EH domain with Rabenosyn-5, a Rab4/Rab5 effector that plays an important role in transport from early endosomes to recycling endosomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EHD1/mRme-1 interacts through its EH domain with an actin-associated protein EHBP1 that, like EHD1/mRme-1 itself, is required for insulinstimulated translocation of the GLUT4 to the plasma membrane (13). Finally, EHD1/mRme-1 has been shown to interact through its EH domain with Rabenosyn-5, a Rab4/Rab5 effector that plays an important role in transport from early endosomes to recycling endosomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…Gene Knockdown by Silencing RNA (siRNA)-Custom design oligonucleotide duplexes targeting human EHD1 (Naslavsky et al (15)) and ON-TARGETplus SMARTpool siRNA targeting MICAL-L1 and Crmp2 (Dharmacon) were transfected for 72 h using Dharmafect (Dharmacon) as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have determined that the EH domains of the C-terminal EHD proteins have a highly positively charged surface (12) and selectively interact with NPF motifs followed by clusters of acidic residues (13,14). Moreover, EHD proteins coordinate endocytic transport with Rab proteins through their interactions with common effectors that contain such NPF motifs (9,15). More recently, it was demonstrated that EHD1 interacts with the NPF-containing MICAL family protein, MICAL-L1, a Rab8 effector that localizes to EHD1-containing tubules and regulates endocytic transport and recycling (16).…”
mentioning
confidence: 99%
“…Rab GTPases and Rab effectors are tightly linked in all components of the endosomal trafficking system, and have long been known to coordinate vesicular trafficking (65,66). Furthermore, both Rab and Rab effectors are known binding partners of EHD proteins (46,(67)(68)(69). Currently, there are Ͼ60 Rab GTPases with an equal number of Rab effectors.…”
Section: Discussionmentioning
confidence: 99%
“…EHD3 Co-immunoprecipitates with Cav3.1 and Cav3.2-In non-cardiac tissue, EHD proteins are linked with a host of membrane ion channels, transporters, and receptors (4,(45)(46)(47)(48). However, loss of Ca V 3.1 and Ca V 3.2 expression and targeting in EHD3 cKO atria may represent an indirect response to myocyte remodeling in the face of altered cell trafficking pathways.…”
Section: Ehd3 Is Required For Ca V 31 and Ca V 32 Targeting In Atrialmentioning
confidence: 99%